The Relationship between Slack Resources and the Performance of Entrepreneurial Firms: The Role of Venture Capital and Angel Investors - Vanacker, Tom; Collewaert, Veroniek; Paeleman, Ine (Journal of Management Studies, 2013)
AbstractIn this study, we seek to further delineate factors that condition the relationship between slack resources and firm performance. To do so, we develop and test a model that establishes the role of venture capital (VC) and angel investors as powerful external stakeholders who positively moderate the slack–performance relationship. In addition, we provide more insight into this relationship by examining differences between these two types of private investors and by examining the role of their ownership stakes. We test our hypotheses using a sample of 1215 private firms, including VC‐backed firms, angel‐backed firms, and similar firms without such investors. We find that the presence of VC investors positively moderates the relationship between both financial and human slack resources and firm performance, while angel investors only positively moderate the effect of human resource slack. Further, VC investors are only marginally better at helping entrepreneurs to extract value from human resource slack than angel investors and they are no better when it comes to financial slack. Finally, we find that the impact of financial and human resource slack on firm performance is more positive in VC‐backed firms when investors hold high ownership stakes, an effect which is significantly stronger than when angel investors hold high ownership stakes.